Overexpression Cathepsin D Contributes to Perineural Invasion of Salivary Adenoid Cystic Carcinoma - Zhang, Mei; Wu, Jia-shun; Yang, Xiao; Pang, Xin; Li, Li; Wang, Sha-sha; Wu, Jing-biao; Tang, Ya-jie; Liang, Xin-hua; Zheng, Min; Tang, Ya-ling (Frontiers in Oncology, 2018)
Abstract Objective: Cathepsin D (CTSD) is a pivotal orchestrator in the occurrence and development of tumors. Recently, CTSD was detected in salivary adenoid cystic carcinoma (SACC). However, its functional role in perineural invasion (PNI) of SACC remained elusive. We conducted the present study to detect the expression of CTSD in SACC, analyze the correlation between CTSD expression and prognosis of SACC patients and elucidate the role of CTSD in occurrence of PNI in SACC to lay the foundation for further studies. Methods: Immunohistochemical analysis was conducted to assess CTSD and Ki67 expression in 158 SACC samples and 20 normal salivary gland samples adjacent to carcinoma. Meanwhile, the correlation between CTSD and PNI of SACC specimens was analyzed using Chi-squared test. QRT-PCR, immunoﬂuorescence and western blot analysis were used to examine the levels of CTSD mRNA and protein in SACC-LM cell line. SiRNA-mediated CTSD silence was performed. Scratch wound healing assay, transwell invasion assay and DRG co-culture assay of PNI was used to detect the ability of migration, invasion and PNI. FITC-phalloidin was used to detect cytoskeletal organization. Results: Our data demonstrated that the positive expression of CTSD was observed in 74.1% (117/158) of SACC cases, and the expression of CTSD was significantly correlated with the PNI (P<0.05). The ability of migration, invasion and PNI could be inhibited significantly by siRNA-mediated CTSD silence (P<0.01). Furthermore, siRNA-mediated CTSD silence inhibited cytoskeletal organization and pseudo foot formation in SACC-LM cells. Conclusion: Our results suggested that an association between PNI and expression of CTSD existed. CTSD may promote PNI of SACC accompanied by cytoskeletal organization and pseudo foot formation.